2019
DOI: 10.1038/s41598-019-44107-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Septoplasty with Inferior Turbinectomy as an In-patient or Out-patient Procedure

Abstract: The study aimed to compare the surgical outcomes of septoplasty with inferior turbinectomy between in-patient and out-patient groups. A total of 152 patients who underwent septoplasty with inferior turbinectomy between May 2012 and February 2013 were retrospectively reviewed and divided into in-patient group and out-patient group. The two groups were compared in three aspects: (i) consumption of medical resources, including National Health Insurance payments, patient surcharges, and total surgical expenses; (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…15 The reported incidence of NAs in the literature varies, with estimates ranging from 0% to 19.7% following septoplasty with submucous turbinate surgery. [16][17][18][19] Patients that develop NAs postoperatively may suffer from iatrogenic NAO and persistent sinonasal symptoms. 9 A study by Henriquez et al of 286 patients, including those that underwent septoplasty, demonstrated that those who developed NAs following surgery experienced significantly poorer Rhinosinusitis Disability Index (RSDI) and Chronic Sinusitis Survey (CSS) scores compared to those that did not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The reported incidence of NAs in the literature varies, with estimates ranging from 0% to 19.7% following septoplasty with submucous turbinate surgery. [16][17][18][19] Patients that develop NAs postoperatively may suffer from iatrogenic NAO and persistent sinonasal symptoms. 9 A study by Henriquez et al of 286 patients, including those that underwent septoplasty, demonstrated that those who developed NAs following surgery experienced significantly poorer Rhinosinusitis Disability Index (RSDI) and Chronic Sinusitis Survey (CSS) scores compared to those that did not.…”
Section: Introductionmentioning
confidence: 99%
“…15 The reported incidence of NAs in the literature varies, with estimates ranging from 0% to 19.7% following septoplasty with submucous turbinate surgery. 1619…”
Section: Introductionmentioning
confidence: 99%
“…1 It can be done under general anaesthesia or as an out-patient surgery with good cost-effectiveness, satisfactory quality, and good safety and patient satisfaction. 3 With the advent of rigid endoscopes in the clinical practise of otorhinolaryngologists, advances have been made in septal surgery as well, with more focus on tissue preservation and minimal invasion. Although both conventional and endoscopic procedures aim to remove the deviated part of the septum, increasing focus has been placed on septal preservation, realignment, or a mix of the two.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of adhesions following septoplasty with submucous turbinate surgery estimates 0-19.7% occurrence (Naghibzadeh et al, 2011;Deniz et al, 2014;Chen and Huang, 2019;Joshi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%